The Lemnaceae of La Pampa province, Argentine (Semiárida, 2020)
In this contribution, three genera and eight species of Lemnaceae growing in the province of La Pampa, Argentine, are keyed, described and illustrated. One genus: Wolffia Horkel and five species: Lemna parodiana Giardelli, Lemna dispersa lIegelmaier, Lemna minima Philippi, Wolffia papulifera Thompson y Wolffia columbiana Karsten are mentioned for the first time to this region.